Urgensi Program Pengembangan Kompetensi SDM secara berkesinambungan di Lingkungan Instansi Pemerintah - Raden Yudhy Pradityo Setiadiputra (Program Studi Administrasi Negara Universitas Serang Raya, 2017)
Urgency of Sustainable Human Resource Development Program in Government Institution Competence is the ability of every human resources work that includes aspects of knowledge, skills and work attitude that is absolutely necessary in carrying out its duties. Development of this competency is done to meet the competency gap. With the development of competence is expected to balance the competence of each employee with the standard of competence of the employee. The purpose of this study is to know the urgency of competency development program Human Resources in continuous Environment Government Institutions. The research method used is qualitative approach with descriptive method. Technique of data collection is done by searching the document of regulation and review literature. The result and discussion in this research is the need for competence development to produce professional ASN, have basic value, professional ethics, free from political intervention, clean from corruption, collusion and nepotism. Government agencies to fulfill the right of each ASN will be bigger and required work units that have the main duties, functions and functions of developing human resource competencies. Human resource competency development programs in government agencies should be carried out continuously. This is because the development of competence is an obligation that must be done by every government agency to fulfill the right of each ASN. Continuous programs will produce targeted and clear outputs in determining follow-up on implementation.